Morton, T. & Boyer, D (2021). Hyposubjects: On becoming human. Open Humanities Press. - Robertson, Nicola (Journal of Posthumanism, 2022)
In the opening of their book Hyposubjects: On becoming human, Morton and Boyer (2021) prepare their reader that “what follows is an exercise in flimsy and chaotic thinking” (13). As introductions go, it is certainly unusual, irreverent and an astute assessment of how the book unfolds.